Epidemiological aspects of brain and head injuries treated at the Hospital Regional do Agreste de Pernambuco from 2006 to 2007 - doi:10.5020/18061230.2010.p4 - Ramos, Emília Maria Santos (2012)
Objective: To identify the prevalence of traumatic brain injury (TBI) and related factors in victims treated at the Hospital Regional do Agreste de Pernambuco (HRA-PE) and characterize the sociodemographic profile of the victims. Method: This is a documentary study with individual data collection from hospital records of patients who were admitted to the HRA-PE with a diagnosis of TBI in the years 2006 and 2007. The variables studied were: prevalence of cases, origin of victims, sex, age, cause-related trauma and neurological symptoms from the Glasgow scale. Results: The sample consisted of records of 171 victims. The largest number of cases occurred in 2007, with 125 (73.1%) cases. Of the cases reported 139 (81.4%) were male, 92 (53.8%) were single and 45 (26.3%) were in the range of 21-30 years old. Falling was the cause of trauma in 52 (30.4%) cases, followed by 34 (19.9%) cases of motorcycle accidents. Vascular injuries occurred in 55 (32.2%) cases, with greater frequency then nerve and bone injuries, occurring in 39 (22.8%) and 34 (19.9%) cases, respectively. The average Glasgow Coma Scale was 11 + 4. Of the total sample surveyed, 20 (11.7%) patients were intoxicated at the time of trauma, 106 (62%) needed conservative treatment and 18 (10.5%) subsequently died. Conclusion: There was a high prevalence of traumatic brain injury at the HRA-PE in the years 2006 and 2007, with a predominance of young single male victims. Alcohol consumption was found in a representative percentage of the victims and the most frequent injuries were caused by falls and motorcycle accidents.